New species of Tobantilla Casal, 1965 and a new genus and species, Gogoltilla chichikovi gen. et sp. nov., from Argentina (Hymenoptera: Mutillidae) - Williams, Kevin A.; Brothers, Denis J.; Pitts, James P. (Zootaxa, 2011)
Seven new species of Tobantilla Casal are described: T. aleatrix Williams, Brothers & Pitts, sp. nov. (Argentina), T. andrikos Williams, Brothers & Pitts, sp. nov. (Colombia), T. drosos Williams, Brothers & Pitts, sp. nov. (Argentina), T. ephemeros Williams, Brothers & Pitts, sp. nov. (Argentina, Uruguay), T. kolasma Williams, Brothers & Pitts, sp. nov. (Venezuela), T. krima Williams, Brothers & Pitts, sp. nov. (Colombia), and T. xouthos Williams, Brothers & Pitts, sp. nov. (Venezuela). Four of these species represent the first males described in Tobantilla. Tobantilla frigidula (Cresson), comb. nov. and the two original members of Tobantilla, T. charrasca Casal and T. montonera Casal, are redescribed. A new genus that is apparently closely related to Pseudomethoca Ashmead, but closely resembles Tobantilla, is described: Gogoltilla Williams, Brothers & Pitts, gen. nov., based on both sexes of Gogoltilla chichikovi Williams, Brothers & Pitts, sp. nov. (Argentina).